-5x+3=-x-1

Simple and best practice solution for -5x+3=-x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x+3=-x-1 equation:


Simplifying
-5x + 3 = -1x + -1

Reorder the terms:
3 + -5x = -1x + -1

Reorder the terms:
3 + -5x = -1 + -1x

Solving
3 + -5x = -1 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
3 + -5x + x = -1 + -1x + x

Combine like terms: -5x + x = -4x
3 + -4x = -1 + -1x + x

Combine like terms: -1x + x = 0
3 + -4x = -1 + 0
3 + -4x = -1

Add '-3' to each side of the equation.
3 + -3 + -4x = -1 + -3

Combine like terms: 3 + -3 = 0
0 + -4x = -1 + -3
-4x = -1 + -3

Combine like terms: -1 + -3 = -4
-4x = -4

Divide each side by '-4'.
x = 1

Simplifying
x = 1

See similar equations:

| 16-v=13 | | 3(2x+4)8x=40 | | Ay-C=Bx | | 8m-25=27 | | 2x-1y=8 | | 3x=4y+5 | | 4w+11=55 | | 11=-x+6 | | 5y=-4x+6 | | -3x=10+2x | | 2x-(x+3)=2x-11 | | -3(x+8)+3=11(x-7) | | 13-6x+14= | | X^2+60x-252=0 | | 180-3x=12x | | x(x^2-4x+75)=0 | | F(x)=4x^9 | | 8.1+9=5.1x-3 | | zi+z+1+3i=0 | | 24X+1.19=.79 | | 51=4w-17 | | 47=2u+13 | | 24X+0.79=1.19 | | -7x+2y=9fory | | x+14=4x-9 | | 2(x+3)-x+4=2(x-1)+5 | | 5u+15=60 | | 9x=4x-8+2 | | -7x+2y=9foru | | i*z+z+1+3*i=0 | | (5x-12)=2 | | 8ty=4 |

Equations solver categories